2018
DOI: 10.2355/isijinternational.isijint-2017-614
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coiling Temperature on Microstructure and Precipitation Behavior in Nb–Ti Microalloyed Steels

Abstract: This paper presents our latest studies on the effects of coiling temperature on the microstructure, precipitation behavior, and mechanical properties of an Nb-Ti microalloyed steel produced by endless strip processing (ESP) and coiled at different temperatures. The amounts of soluble elements were measured using inductively coupled plasma optical emission spectrometry (ICP-OES). The microstructure and precipitates were analyzed using SEM, EBSD, TEM, and electrolytic dissolution and filtration tests. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The second type (P2) is verified as cementite mainly distributed in the grain boundaries. According to the previous studies [ 18 , 19 ], these (Ti, Mo, V)C particles are mainly precipitated during the soaking at high temperature.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The second type (P2) is verified as cementite mainly distributed in the grain boundaries. According to the previous studies [ 18 , 19 ], these (Ti, Mo, V)C particles are mainly precipitated during the soaking at high temperature.…”
Section: Resultsmentioning
confidence: 97%
“…The supersaturated solute microalloying elements will further precipitate in the ferrite during the coiling process. Compared to austenite, the precipitation precipitated in ferrite is smaller in size, thereby producing stronger precipitation strengthening [ 18 , 19 , 26 ]. It should be noted that the contents of solid solution of microalloying elements and carbon in the austenite at 860 °C are used as the initial content in the ferrite calculation model.…”
Section: Resultsmentioning
confidence: 99%
“…At present, industrialized developed countries regard microalloyed steel as the most important research and development direction in the iron and steel industry. [1][2][3][4][5] Previous studies have shown that adding Ti, V, and Nb elements separately or jointly can refine the structure and enhance precipitation strengthening. [6,7] Based on the Ashby-Orowan equation, [8] the size of the precipitation significantly affects the precipitation strengthening.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding thermomechanically processed and controlled cooled high-strength strip steels, the role of processing parameters such as soaking temperature, start-and finish-rolling temperatures, rolling reduction ratio, cooling start-and end temperatures and cooling rate on the microstructure and mechanical properties have been studied extensively [4][5][6]. It is noteworthy that UHSS strips (< 10 mm thickness) are usually coiled after finish rolling, and use accelerated cooling to a lower temperature range (typically, 350 -460 C) to achieve high strength by the formation of bainite-martensite mixed microstructures [7][8][9][10][11][12][13]. An increase in strength, however, is often accompanied by a decrease in ductility and impact toughness [14].…”
Section: Introductionmentioning
confidence: 99%